Dual DC Motor Speed Control Based on Two Independent Digital PWM Signals using PIC16F877A Microcontroller - Ayman Y. Yousef; M. H. Mostafa (Institute of Advanced Engineering and Science, 2016)
In this paper a dual open loop speed control system based on two independent PWM signals of small permanent magnet DC (PMDC) motors using PIC16F877A microcontroller (MCU) has been designed and implemented. The Capture/Compare/PWM (CCP) modules of the MCU are configured as PWM mode and the MCU is programmed using flowcode software package to generate two PWM signals with various duty cycles at the same frequency. A dual H-bridge channel chip SN754410 is used to drive the motors. The variation of PWM duty cycles is related directly to controlling the DC motors terminal voltage which directly proportional with speed of each motor. The complete PWM control system model has been simulated using proteus design suite software package. The development of hardware and software of the dual DC motor speed control system has been explained and clarified.